The battle cry of peace: the leadership of the disciples of Christ movement during the American Civil War, 1861-1865 - Tuck, Darin A. (Kansas State University, 2010)
As the United States descended into war in 1861, the religious leaders of the nation were among the foremost advocates and recruiters for both the Confederate and Union forces. They exercised enormous influence over the laity, and used their sermons and periodicals to justify, promote, and condone the brutal fratricide. Although many historians have focused on the promoters of war, they have almost completely ignored the Disciples of Christ, a loosely organized religious movement based on anti-sectarianism and primitive Christianity, who used their pulpits and periodicals as a platform for peace. This study attempts to merge the remarkable story of the Disciples peace message into a narrative of the Civil War. Their plea for nonviolence was not an isolated event, but a component of a committed, biblically-based response to the outbreak of war from many of the most prominent leaders of the movement. Immersed in the patriotic calls for war, their stance was extremely unpopular and even viewed as traitorous in their communities and congregations. This study adds to the current Disciples historiography, which states that the issue of slavery and the Civil War divided the movement North and South, by arguing that the peace message professed by its major leaders divided the movement also within the sections. In fact, by the outbreak of war, the visceral debates that occurred among the Disciples leadership did not center on the issue of slavery, constitutionality of secession, or even which belligerent was in the right. The chief point of contention was whether a Christian, based on New Testament precepts, could participate in war. The nonviolent leaders thought that their peace message derived from the New Testament would be the one thing that would preserve unity in the brethren. In reality, it became the primary source of division.
Keywords: Civil War; Disciples of Christ; Pacifism; Nonviolence; History, Church (0330); History, United States (0337)